2013
DOI: 10.3897/compcytogen.v7i4.6012
|View full text |Cite
|
Sign up to set email alerts
|

Extensive fragmentation of the X chromosome in the bed bug Cimex lectularius Linnaeus, 1758 (Heteroptera, Cimicidae): a survey across Europe

Abstract: Variation in the number of chromosomes was revealed in 61 samples of Cimex lectularius Linnaeus, 1758 from the Czech Republic and other European countries, hosted on Myotis Kaup, 1829 (4) and Homo sapiens Linnaeus, 1758 (57). The karyotype of all the specimens of Cimex lectularius analysed contained 26 autosomes and a varying number of the sex chromosomes. The number of sex chromosomes showed extensive variation, and up to 20 fragments were recorded. Altogether, 12 distinct karyotypes were distinguished. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 30 publications
2
44
0
Order By: Relevance
“…The numbers of C. lectularius X chromosomes can differ among different populations (localities), or among specimens within one population. Even a single specimen can contain cells with different numbers of X chromosomes (Ueshima 1966, 1979, Sadílek et al 2013. Preliminary study has also indirectly indicated the possibility of a variable number of X chromosomes in an obligatory bat parasite Cimex pipistrelli Jenys, 1839 (Sadílek et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The numbers of C. lectularius X chromosomes can differ among different populations (localities), or among specimens within one population. Even a single specimen can contain cells with different numbers of X chromosomes (Ueshima 1966, 1979, Sadílek et al 2013. Preliminary study has also indirectly indicated the possibility of a variable number of X chromosomes in an obligatory bat parasite Cimex pipistrelli Jenys, 1839 (Sadílek et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Even a single specimen can contain cells with different numbers of X chromosomes (Ueshima 1966, 1979, Sadílek et al 2013. Preliminary study has also indirectly indicated the possibility of a variable number of X chromosomes in an obligatory bat parasite Cimex pipistrelli Jenys, 1839 (Sadílek et al 2013). Therefore, it seems possible that intraspe-cific variability of X chromosomes could be a general feature of the genera Cimex and Paracimex Kiritshenko, 1913, or even possibly a wider spectrum of Cimicidae species.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations